Psychology in Schools: Human Rights and Constitution of Subjectivity in the School Context (Interdisciplinary Studies Journal, 2021)
This article is the result of research whose central theme was the violation of human rights and the construction of subjectivity in the school context, considering the contribution of Psychology. The general objective of the research was, therefore, to understand how the exercise of these rights influences the construction of subjectivity in schools and the role of Psychology in this context. To achieve this objective, a bibliographical research was developed, defined as one that seeks theoretical references already published or prior knowledge about the phenomenon under investigation. Initially, an exploratory research was necessary, which, as such, provided not only a broader view but also an approach to this still little-explored theme, which constitutes a challenge in research. As a methodological strategy, we used a time frame for the articles, books, theses, and other works found, both physical and electronic, selecting those published between 1989 and 2019. In this way, we would historically follow the theme of human rights. In this article, as in the research, we used as the central theoretical reference the work of Vygotsky, an author who draws from Marx's historical and dialectical materialism. As results, we observed that subjectivity is constituted from the material, political, economic, historical, and social context. The school was the focus of the investigation, as it is understood here as a sociocultural space that also serves a social function and the transformation of individuals. We identified the rights of children and adolescents based on Brazilian legislation and found that their exercise or violation can have effects on the construction of subjectivity. Thus, we highlight the importance of the Psychology professional in schools and in Public Education Policies, considering their role and social commitment to the less privileged Brazilian population and to ensuring the exercise of human rights in the school environment.
Keywords: Human Rights; School; Subjectivity